Experiments and modeling of atmospheric pressure microwave plasma reforming of a methane-carbon dioxide mixture. Issue 46 (April 2021) - Sun, Hojoong; Lee, Jungwun; Bak, Moon Soo
Highlights: A dry reforming of CH4 was conducted using electrodeless microwave plasmas at atmospheric pressure. CH4 and CO2 conversion efficiencies of 96% and 91% were achieved with CO and H2 selectivity of more than 95%. The gas temperature in the plasma reached about 5500 K, indicating local heating of the feed gas by the plasma. A reactor network model is developed, analyzing the effect of local gas heating by plasma on the reforming performance. Abstract: Atmospheric pressure microwave plasma reforming was conducted on a methane (CH4 ) and carbon dioxide (CO2 ) mixture, and characterized by measuring the temperature of the plasma and gas composition of the reforming product via optical emission spectroscopy (OES) and gas chromatographic measurement. The temperature at the plasma reached as high as 5900 K regardless of the specific energy input, while at microwave power of 2 kW and flow rate of 10 slm, nearly all CH4 and CO2 were converted into hydrogen (H2 ) and carbon monoxide (CO). The plasma temperature higher than the level achievable from uniform gas heating implied that only a part of the flow will enter the plasma region, and the rest will bypass and mix with the plasma stream downstream. Thus, a reactor network-type simulation was performed by modeling the plasma and surrounding streams, each as a series of perfectly-stirred reactors; the reactors at the same downstream locations interacted for the gas diffusion and heat conduction. The simulation reproduced the measured gas compositions well, revealing that the reforming proceeded as the surrounding gas enters and diffuses out of the plasma stream due to the flow mixing, as well as through the heating of the surrounding stream by the plasma stream.